Compatible Mycorrhizal Types Contribute to a Better Design for Mixed Eucalyptus Plantations - Qin, Fangcuo; Yu, Shixiao (Frontiers in Plant Science, 2021)
A mixed-species forest is a sound option to facilitate ecological restoration, plant diversity and ecosystem functions. Compatible species combinations are conducive to reconstruct plant communities that can persist at a low cost without further management and can even develop into natural forest communities. However, our understanding of how the compatibility of mycorrhizal types mediates species coexistence is still limited, especially in a novel agroforest system. Here, we assessed the effects of mycorrhizal association types on the survival and growth of native woody species in mixed-species Eucalyptus plantations. We conducted pot experiments to uncover how mycorrhizal types regulate the strength and direction of plant-soil feedbacks by treating distinct mycorrhizal plants with soil microbes from their own or other mycorrhizal types. We then compared the growth response of arbuscular mycorrhizal plants and ectomycorrhizal plants to different microbial compositions associated with Eucalyptus plants. We found that the type of mycorrhizal association had a significant impact on the survival and growth of native tree species in the mixed plantations. The strength and direction of the plant-soil feedback of focal tree species depend on mycorrhizal types. Non-mycorrhizal plants had consistent negative feedbacks with the highest survival in the Eucalyptus plantations, whereas nitrogen-fixing plants experienced consistent positive feedbacks and the lowest survival. Arbuscular mycorrhizal and ectomycorrhizal plants had varied feedback responses to soil microbes from distinct mycorrhizal plant species. Non-mycorrhizal plants grew better with Eucalyptus soil microbes while nitrogen-fixing plants grew worse with their own conspecific soil microbes. The soil microbial community induced by Eucalyptus resulted in a greater increase in the aboveground growth of arbuscular mycorrhizal plants, but the non-mycorrhizal composition of the Eucalyptus soil microbial community resulted in greater belowground growth of ectomycorrhizal plants. Overall, Eucalyptus plants induced an unfavorable soil community, impeding coexistence with other mycorrhizal plants. Our study provides observational and experimental evidence that the type of mycorrhizal association, through a change in plant-soil microbial feedbacks, determines species coexistence among woody species in multi-species plantations.